Violence and Public Safety as a Democratic Simulacrum in Brazil - Lima, Renato Sérgio de (International Journal of Criminology and Sociology, 2018)
This paper analyzes actions taken by eight special programs for homicide reduction implemented in the states of Bahia, Ceará, Espírito Santo, Minas Gerais, Pernambuco, Rio de Janeiro and São Paulo, as well as the Brazilian Federal District. It aims to understand the historical permanence of lethal violence as one of the most striking social characteristics of Brazil and defends the argument that the prevention and tackling of homicides – understood in a broad sense that includes all intentional violent deaths – are operated, both politically and institutionally, from a symbolic simulacrum that causes incremental initiatives to fail to reach the architecture of criminal justice and public security institutions. As structural reforms in the criminal justice and public security system face several obstacles to being approved by the Legislative Branch, this simulacrum makes the police force and other institutions belonging to the system to continue operating from a center of criminal policies that do not depend on the construction of a democratic project of public security, protection of life or civil and human rights. The study reiterates that the debate on transparency and data quality can allow actions to strengthen institutional capacity for monitoring and evaluation and/or strategic litigation, which in turn may weaken of the path dependence and worldviews that operate the identified simulacrum. In other words, the debate on transparency and data quality is one of the strongest battlefronts for the reduction of violence and for the democratization of public safety in Brazil.